Identification of factors associated with sarcopenic obesity development: Literature review and expert panel voting - Pinel, A; Guillet, C; Capel, F; Pouget, M; De Antonio, M; Pereira, B; Topinkova, E; Eglseer, D; Barazzoni, R; Cruz-Jentoft, A J; Schoufour, J D; Weijs, P J M; et al. (Clinical nutrition (Edinburgh, Scotland), 2024)
Sarcopenic obesity (SO) is defined as the combination of excess fat mass (obesity) and low skeletal muscle mass and function (sarcopenia). The identification and classification of factors related to SO would favor better prevention and diagnosis. The present article aimed to (i) define a list of factors related with SO based on literature analysis, (ii) identify clinical conditions linked with SO development from literature search and (iii) evaluate their relevance and the potential research gaps by consulting an expert panel. From 4746 articles screened, 240 articles were selected for extraction of the factors associated with SO. Factors were classified according to their frequency in the literature. Clinical conditions were also recorded. Then, they were evaluated by a panel of expert for evaluation of their relevance in SO development. Experts also suggested additional factors. Thirty-nine unique factors were extracted from the papers and additional eleven factors suggested by a panel of experts in the SO field. The frequency in the literature showed insulin resistance, dyslipidemia, lack of exercise training, inflammation and hypertension as the most frequent factors associated with SO whereas experts ranked low spontaneous physical activity, protein and energy intakes, low exercise training and aging as the most important. Although literature and expert panel presented some differences, this first list of associated factors could help to identify patients at risk of SO. Further work is needed to confirm the contribution of factors associated with SO among the population overtime or in randomized controlled trials to demonstrate causality.
Keywords: kosterní svaly; Risk factors; Aging; Obesity; Chronic diseases; lidé; cvičení; Muscle, Skeletal; hlasování; Disability; Risk Factors; obezita; Voting; Insulin Resistance; stárnutí; inzulinová rezistence; rizikové faktory; sarkopenie; Exercise; Sarcopenia; Humans